DOAB Directory of open access books (OAPEN, OpenEdition, CNRS and Aix-Marseille Université, provided by DOAB Foundation, 2020)
Open Access Books is a joint service of OAPEN, OpenEdition, CNRS and Aix-Marseille Université.